Optimizing EFL Learners’ Writing Learning Processes through Automated Writing Evaluation - Wijaya, Kristian Florensio (Cognitive Insight in Education, 2025)
This small-scale library study explores the role of Automated Writing Evaluation (AWE) in optimizing EFL learners’ writing processes. The researcher employed thematic analysis to analyze findings from 30 peer-reviewed journal articles published between 2019 and 2024. Data were coded using an open-coding strategy and grouped into overarching themes. Two dominant themes emerged: (1) AWE enhanced EFL learners' writing skills, and (2) AWE cultivated writing autonomy. These findings suggest that AWE facilitates more independent, confident, and proficient writing practices. Implications for integrating AWE tools into EFL classrooms and directions for future research are discussed.